1993
DOI: 10.1007/bf01525437
|View full text |Cite
|
Sign up to set email alerts
|

In vivo modulation of natural killer cell activity by tamoxifen in patients with bilateral primary breast cancer

Abstract: Natural killer (NK) cell activity, the autologous mixed lymphocyte reaction (AMLR) and proportions of T cell subpopulations (CD3+/CD4+ and CD3+/CD8+) and NK cells (CD16+) were studied in 21 patients with bilateral primary breast cancer (BBC), 10 patients with single-breast cancer (SBC) and 20 healthy controls. All patients studied had no evidence of disease and had been off radiotherapy and/or chemotherapy for at least 1 year. Ten patients with BBC were also treated with tamoxifen. Patients with SBC had NK cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…To gain more insights into antiestrogeninduced resistance, we have addressed whether antiestrogeninduced TGFβ could contribute to resistance development due to its well-known functions as an immune regulator. When peripheral blood lymphocytes of breast cancer patients were analyzed, antiestrogens apparently displayed only weak direct effects both with respect to function and quantity of circulating lymphocytes (23,24). However, the consequences of antiestrogen treatment on the interaction of tumor cells with its immediate surrounding tissue, composed of stromal fibroblasts, endothelial cells, and a variety of infiltrating immune cells, are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…To gain more insights into antiestrogeninduced resistance, we have addressed whether antiestrogeninduced TGFβ could contribute to resistance development due to its well-known functions as an immune regulator. When peripheral blood lymphocytes of breast cancer patients were analyzed, antiestrogens apparently displayed only weak direct effects both with respect to function and quantity of circulating lymphocytes (23,24). However, the consequences of antiestrogen treatment on the interaction of tumor cells with its immediate surrounding tissue, composed of stromal fibroblasts, endothelial cells, and a variety of infiltrating immune cells, are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Rotstein et al and subsequently Robinson et al reexamined the effects of tamoxifen on immunity in breast cancer patients and demonstrated modulatory effects [19,20]. Rotstein et al studied the function of peripheral lymphocytes derived from breast cancer patients (n=23) treated with tamoxifen for 1.5 to 2 years [19].…”
Section: Tamoxifen As An Immune Modulatormentioning
confidence: 99%
“…NCA against NK-sensitive K562 cells was tested, as previously described, 23,24 at E:T ratios of 50:1, 25:1 and 12:1. NCA is also presented as the number of LUs in 10 7 effector cells (1 LU is the number of effector cells that lyse 20% of target cells).…”
Section: Nca Assaymentioning
confidence: 99%